Extremophilic yeasts: the toughest yeasts around?. Issue 8 (21st May 2018) - Buzzini, Pietro; Turchetti, Benedetta; Yurkov, Andrey
Abstract: Microorganisms are widely distributed in a multitude of environments including ecosystems that show challenging features to most life forms. The combination of extreme physical and chemical factors contributes to the definition of extreme habitats although the definition of extreme environments changes depending on one's point of view: anthropocentric, microbial‐centric or zymo‐centric. Microorganisms that live under conditions that cause hard survival are called extremophiles. In particular organisms that require extreme conditions are called true extremophiles while organisms that tolerate them to some extent are termed extremotolerant. Deviation of temperature, pH, osmotic stress, pressure and radiation from the common range delineates extreme environments. Yeasts are versatile eukaryotic organisms that are not frequently considered the toughest microorganisms in comparison with prokaryotes. Nevertheless extremophilic or extremotolerant species are present also within this group. Here a brief description is provided of the main extreme habitats and the metabolic and physiological modifications adopted by yeasts depending on their adverse conditions. Additionally the main extremophilic and extremotolerant yeast species associated with a few extreme habitats are listed. Abstract : Deviation of temperature, pH, osmotic stress, pressure, and radiation from the common range delineates extreme environments. Organisms including yeasts that require extreme conditions are called true extremophiles while organisms that tolerate them to some extent are termed extremotolerant. Extremophilic or extremotolerant yeasts exhibit metabolic and physiological modifications to overcome the adverse effects of extreme conditions.